2007
DOI: 10.1073/pnas.0705834104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a peripheral blood transcriptional biomarker panel associated with operational renal allograft tolerance

Abstract: Long-term allograft survival generally requires lifelong immunosuppression (IS). Rarely, recipients display spontaneous ''operational tolerance'' with stable graft function in the absence of IS. The lack of biological markers of this phenomenon precludes identification of potentially tolerant patients in which IS could be tapered and hinders the development of new tolerance-inducing strategies. The objective of this study was to identify minimally invasive blood biomarkers for operational tolerance and use the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
312
1
16

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(345 citation statements)
references
References 54 publications
16
312
1
16
Order By: Relevance
“…Thus, in specific circumstances, the information provided by gene expression analyses may be used to enhance rather than replace that provided by graft pathology. Finally, in common with the work published by others in the field, 18,20,23,25,29,40,54,56 our TLDA and microarray analyses contribute to a growing publicly available databank of expression profiles from KTx recipients with diverse characteristics and provide a basis for ongoing mechanistic investigation of renal allograft injury and repair.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, in specific circumstances, the information provided by gene expression analyses may be used to enhance rather than replace that provided by graft pathology. Finally, in common with the work published by others in the field, 18,20,23,25,29,40,54,56 our TLDA and microarray analyses contribute to a growing publicly available databank of expression profiles from KTx recipients with diverse characteristics and provide a basis for ongoing mechanistic investigation of renal allograft injury and repair.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies, including our own, have suggested gene expression signatures of tolerance in kidney transplantation 7, 8, 9, 11, 32 or have described differential expression of smaller gene sets 11, 33, 34. None had assessed the confounding effect of IS.…”
Section: Discussionmentioning
confidence: 99%
“…22,[33][34][35] To investigate the possible biologic mechanisms underlying the clinical action of this immunosuppressive drug, we decided to apply an exploratory genomic analysis performed as an hypothesis-generating approach. The transcriptomic screening has been extensively used in transplantation to identify biomarkers for an early diagnosis of acute 36 and chronic rejection, 37 but presently, little is known about the change in the genomic profile induced by pharmacologic intervention in transplant recipients. Microarray analysis showed that 16 genes were modulated by the conversion from AZA to EC-MPS in the immunosuppressive regimen of our renal transplant population.…”
Section: Discussionmentioning
confidence: 99%